2020
DOI: 10.3390/pathogens9080670
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Reassortment of Clade 2.3.4.4 H5N6 Highly Pathogenetic Avian Influenza Viruses Demonstrating High Risk to Public Health

Abstract: Since it firstly emerged in China in 2013, clade 2.3.4.4 H5N6 highly pathogenic avian influenza viruses (HPAIVs) has rapidly replaced predominant H5N1 to become the dominant H5 subtype in China, especially in ducks. Not only endemic in China, it also crossed the geographical barrier and emerged in South Korea, Japan, and Europe. Here, we analyzed the genetic properties of the clade 2.3.4.4 H5N6 HPAIVs with full genome sequences available online together with our own isolates. Phylogenetic analysis showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Recent years have seen the replacement of the H5N1 subtype with H5N6 and H5N8 HPAIVs from the clade 2.3.4.4 as the dominant subtypes in circulation [ 14 , 16 , 21 , 46 , 47 ]. Here, we collected two new H5N6 isolates from nearby sites (90 km away from each other) that demonstrate a high degree of nucleotide similarity.…”
Section: Discussionmentioning
confidence: 99%
“…Recent years have seen the replacement of the H5N1 subtype with H5N6 and H5N8 HPAIVs from the clade 2.3.4.4 as the dominant subtypes in circulation [ 14 , 16 , 21 , 46 , 47 ]. Here, we collected two new H5N6 isolates from nearby sites (90 km away from each other) that demonstrate a high degree of nucleotide similarity.…”
Section: Discussionmentioning
confidence: 99%
“…Genotype C1 was first detected in wild birds in Korea; however, genotype C4 became predominant in wild birds and poultry during epidemics in Korea [14]. The clade 2.3.4.4 H5N6 HPAI viruses have caused outbreaks in poultry in China as a major subtype also causing human infection [22], but this strain has not been identified in Korea since 2017.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study showed that human-derived H5N6 AIVs were highly pathogenic in mice (Pan et al, 2018), and avian-derived H5N6 generally showed variable pathogenicity in mice (Li et al, 2020, Song et al, 2019, Sun et al, 2020. Additionally, it has been reported that the H5N6 AIVs isolated in 2015 had more efficient replication potential and pathogenicity in mice than the AIVs isolated in 2014 (Kang et al, 2018), which might be related to the continuous mutations of the HA gene and the continuous reassortment of the internal genes of the avian H5N6 virus (Sun et al, 2018).…”
Section: Discussionmentioning
confidence: 99%